Comparative susceptibility of Anticarsia gemmatalis Hübner (Lepidoptera: Erebidae) and Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) to insecticides Suscetibilidade comparativa de Anticarsia gemmatalis Hübner (Lepidoptera: Erebidae) e Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) a inseticidas - Buss N.* (2022)
© 2022, Universidade Federal de Santa Maria. All rights reserved.Chrysodeixis includens (Walker) and Anticarsia gemmatalis Hübner are important soybean defoliators. The chemical control of A. gemmatalis has been easier and more effective than that of C. includens. It is hypothesized that C. includens is natural tolerant to insecticides. This study quantified and compare the susceptibility of C. includens and A. gemmatalis to the insecticides flubendiamide, methomyl, and spinetoram. A susceptible population of each species, maintained under laboratory conditions without insecticides selection pressure for more than 17 generations, was used. Ingestion bioassays using five to eight concentrations of each insecticide applied on the artificial diet surface were used to estimate the LC50 and LC99 (LC = Lethal Concentration). The tolerance ratio (TR) was calculated by dividing the LC50 or LC99 of the most tolerant species by the respective value of the most susceptible species. Chrysodeixis includens was more tolerant to all insecticides tested than A. gemmatalis, with TR50 values of 45.9-, 10.0-and 2.6-fold for methomyl, flubendiamide, and spinetoram. These findings indicated that the risk of evolution of resistance may be higher for C. includens than A. gemmatalis due to differential survival when exposed to the same dose of insecticide applied in soybean fields. Therefore, to improve the control of both species, integrated pest management (IPM) and insect resistance management (IRM) strategies should be considered to avoid control failures in field conditions.